멜랑콜리와 토스카: 러시아적 우울의 특수성에 대한 연구 - 이병훈 (연세의사학, 2021)
This thesis is a study on the historical origin of depression in Russia. The purpose of this thesis is to examine the cause of the widespread use of “toska” (тоска), which meant depression, instead of хандра (handra), which meant melancholy, in Russia in the 19th century. My hypothesis is that “toska” not only covered most of the meaning of the term “melancholy” but also expressed that mental state more diversely and vividly, and so it was used more extensively in Russia than the foreign and professional medical term “melancholy.” As can be seen from previous research, most studies on “toska”’ were conducted in the fields of literature and linguistics. On the other hand, there have been few medical approaches to “toska” until recently. This is a disappointment when we recall that “toska” is a word that reflects the specificity of Russian melancholy. The most important thing in this study is to elucidate historically and clinically the relationship between “toska” and depression. In this respect, it can be said that this paper has a certain differentiation from previous studies. In particular, it compares the types and meanings of melancholy in the Russian medical dictionary published in the 19th century with “toska” and examines how the depressed state, emotion, and pain expressed in “toska” overlap with melancholy. Through this comparison, we can understand that the meaning and content of the medical term “melancholy” are not fundamentally different from the feelings and states expressed in “toska.” For this purpose, I mainly use the works of Pushkin, the works of various Russian writers, and Russian proverbs as examples.
Keywords: Toska (тоска); Melancholy; Russian Melancholy; Pushkin; Medicine; 토스카; 멜랑콜리; 러시아적 우울; 푸슈킨; 의학